THE EFFECT OF TAX POLICY ON BUSINESS MARKETING STRATEGY ACTIVITES IN INDOMARET, BANDUNG REGENCY - Budianingsih, Risma; Mulyana, Asep; Rahmawati, Eti (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2026)
This study aims to analyze the influence of tax policies on business marketing activities in modern retail companies, specifically Indomaret. As one of the largest minimarket chains in Indonesia with thousands of outlets spread across Indonesia, Indomaret faces various tax policies, such as Value Added Tax (VAT), income tax, and digital tax regulations, which impact the company's operations and marketing strategies. Tax policies, particularly the implementation of an 11% VAT on retail products, directly impact product pricing and consumer purchasing power. This situation encourages the company to adjust its marketing strategies, such as price promotions, discounts, and advertising cost efficiency, to maintain competitiveness in the market. Furthermore, Indomaret also utilizes its extensive network as part of its service marketing strategy, including providing tax payment facilities for the public, which enhances brand image and consumer trust. The research method used a quantitative approach, with data collection techniques through consumer and business surveys, as well as literature studies related to tax policies and retail marketing. Data analysis was conducted to measure the relationship between tax policy variables and marketing activities, such as pricing, promotion, and distribution strategies. The results indicate that tax policies have a significant influence on business marketing activities at Indomaret. Increasing tax burdens tend to encourage companies to adjust pricing and promotional strategies to remain competitive. Furthermore, tax policy also encourages marketing innovation, particularly in the use of additional services and digitalization to attract consumers. The conclusion of this study indicates that tax policy is a critical external factor in determining retail marketing strategies. Therefore, Indomaret needs to integrate tax planning with its marketing strategy to increase business effectiveness and maintain customer loyalty.